Effect of Urban Particulate Matter on Vocal Fold Fibrosis through the MAPK/NF-κB Signaling Pathway - Won, Ho-Ryun (Int J Mol Sci, 2020)
Particulate matter (PM) is an environmental exposure factor that adversely affects human health. PM is a risk factor for various diseases. However, the mechanism by which PM affects the vocal folds (VF) has not yet been evaluated. Thus, we investigated the cytotoxic effects of PM on human vocal fold fibroblasts (hVFF) and the underlying signaling pathways. hVFF were isolated from human VF. The effect of PM on hVFF, and the underlying mechanism, were analyzed using Western blot, quantitative real-time polymerase chain reaction, and flow cytometry. In addition, a histological evaluation was performed in animal experiments. Cell proliferation decreased after the PM treatment. PM increased the expression of interleukin (IL)-6 and IL-1β. The generation of reactive oxygen species (ROS) in PM-treated hVFF and subsequent activation of the mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) pathways were confirmed. Furthermore, PM increased the expression of fibrosis-related markers and induced the accumulation of collagen in the extracellular matrix. As a result, PM exposure significantly enhances the inflammatory response on VF through the ROS-mediated activation of the MAPK and NF-κB signaling pathways. In addition, PM promotes differentiation into myofibroblasts and induces fibrosis. These results suggest that PM triggers an inflammatory reaction through ROS production and causes VF fibrosis.